PENGARUH SISTEM PEMBELAJARAN ONLINE TERHADAP KEPUASAN BELAJAR MAHASISWA AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA DI MASA PANDEMI COVID-19 - Herlambang, Susatyo - (PRIMA EKONOMIKA, 2020)
Covid-19 pandemic conditions make all work and learning activities done from home online through the internet. The purpose of this study is to find out the satisfaction level of online learning through the internet during the Covid-19 pandemic. The method used in this study is a quantitative method with test calculations using SPSS version 17. This study involved 50 student respondents who participated in the process of learning to teach online through the internet during the Covid-19 pandemic. Data were collected using questionnaires and observations. The test results of R Square (coefficient of determination) in this study amounted to 0.457 or 45.7% (R Square X 100%). This means that the effect of online learning variables on student learning satisfaction during the Covid-19 pandemic is 45.7%, while the remaining 54.3% (100%-45.7%) should be explained by other causative factors derived from outside this regression method. The T-test result shows that T count > T table (6,362 > 2,406), T-Test figures show that there is a direct influence between the level of satisfaction of learning online through the internet during the Covid-19 pandemic. With the increase in online learning through the internet, the satisfaction of learning during the Covid-19 pandemic is also increasing. Keywords: System, Study, Online, Student Satisfaction, Pandemic Covid-19.